Glucocerebrosidase enzyme activity in GBA mutation Parkinson's disease. (June 2016) - Ortega, Roberto A.; Torres, Paola A.; Swan, Matthew; Nichols, William; Boschung, Sarah; Raymond, Deborah; Barrett, Matthew J.; Johannes, Brooke A.; Severt, Lawrence; Shanker, Vicki; Hunt, Ann L.; Bressman, Susan; et al.
Highlights: Glucocerebrosidase mutations are associated with increased Parkinson disease risk. GBA enzyme activity in PD patients with and without GBA mutations was evaluated. GBA enzyme activity in PD was lower in GBA mutation carriers vs. non- GBA carriers. Larger and longitudinal studies of GBA enzyme activity and PD onset are warranted. Abstract: Mutations in the glucocerebrosidase ( GBA1 ) gene, the most common genetic contributor to Parkinson's disease (PD), are associated with an increased risk of PD in heterozygous and homozygous carriers. While glucocerebrosidase enzyme (GCase) activity is consistently low in Gaucher disease, there is a range of leukocyte GCase activity in healthy heterozygous GBA1 mutation carriers. To determine whether GCase activity may be a marker for PD with heterozygous GBA1 mutations ( GBA1 mutation PD, GBA PD), GBA PD patients (n = 15) were compared to PD patients without heterozygous GBA1 mutations (idiopathic PD; n = 8), heterozygous GBA1 carriers without PD (asymptomatic carriers; n = 4), and biallelic mutation carriers with PD (Gaucher disease with PD, GD1 PD; n = 3) in a pilot study. GCase activity (nmol/mg protein/hour) in GD1 PD (median [interquartile range]; minimum–maximum: 6.4 [5.7]; 5.3–11) was lower than that of GBA PD (16.0 [7.0]; 11–40) (p = 0.01), while GCase activity in GBA PD was lower than idiopathic PD (28.5 [15.0]; 16–56) (p = 0.01) and asymptomatic carriers (25.5 [2.5]; 23–27) (p = 0.04). Therefore, GCase activity appears to be a possible marker of heterozygous GBA1 mutation PD, and larger studies are warranted. Prospective studies are also necessary to determine whether lower GCase activity precedes development of PD.